2021
DOI: 10.2139/ssrn.3848357
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Change Materials and Biochar: Some New Composite Materials in Recent Literature

Abstract: A phase change material (PCM) is a substance absorbing and releasing energy at phase transition. The substance is therefore useful for heating and cooling applications. Here we review the recent literature about the use of biochar and PCMs for composite materials, to obtain phase change composites (PCCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…For example, a biodegradable PCM that is encapsulated in a non-biodegradable plastic becomes a non-biodegradable waste" [6]. We have observed that, recently, researches for encapsulation of PCM by biochar, an ecologic material, have been proposed [12].…”
Section: Encapsulationmentioning
confidence: 99%
“…For example, a biodegradable PCM that is encapsulated in a non-biodegradable plastic becomes a non-biodegradable waste" [6]. We have observed that, recently, researches for encapsulation of PCM by biochar, an ecologic material, have been proposed [12].…”
Section: Encapsulationmentioning
confidence: 99%